679 Anxiety and Depression Impacts on The Correlation Between Symptom and Radiological Severity in Patients with Chronic Rhinosinusitis. (4th May 2021) - Ranford, D; Surda, P
Abstract: Introduction: Previous studies have reported little correlation between sino-nasal outcome test (SNOT-22) in chronic rhinosinusitis (CRS) and objective radiological scoring. We investigated whether anxiety and depression, which are highly prevalent in patients with CRS may cause symptom amplification and account for the lack of correlation in previous studies. Method: 100 patients with CRS were evaluated using the General Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), SNOT-22 and Lund Mackay Score (LMS). Results: Overall correlation analysis did not show a significant relationship between SNOT-22 and LMS. Subgroup analysis of patients without anxiety or depression showed a significant correlation between SNOT-22 and LMS. We also observed a significant difference in both median SNOT-22 and LMS between patients who suffered with both anxiety and depression and patients without either. Conclusions: When CRS patients who do not have anxiety and depression are analysed in isolation, or when these conditions are controlled in a multivariable regression, there is a significant correlation between radiological findings and symptom score. This correlation is absent in patients with anxiety and depression. Anxiety and depression should be considered in patients in whom there is a mismatch in symptom and radiological disease severity as it is associated with symptom amplification.